Digestibility and Egg Yolk Pigment Intensity of Local Ducks Fed Shrimps Head Meal, Leucaena Leaf Meal and L-Carnitine Supplementation - T Widiyastuti; CH Prayitno; Sudibya (Animal Production: Indonesian Journal of Animal Production, 2007)
The experiment was conducted to determine the nutrient digestibility and egg yolk pigment intensity of local ducks which fed shrimps head meal, leucaena leaf meal and L-Carnitine supplement. The experimental method used was a Completely Randomized Design (CRD) with four treatments i.e : R0 (feed with leucaena leaf meal), R1 (feed with 25 ppm L-Carnitine supplement), R2 (feed with 2% shrimps head meal) and R3 (feed with 4% shrimps head meal). A total of 0,20% FeSO4/kg feed were supplemented to all treatments. The results showed that L-Carnitine supplements and fed shrimps head meal (2% and 4%) have no significant effects (P>0,05) on crude fat and crude protein digestibility but have significant (P<0.05) effects on yolk pigment intensity. L-Carnitine supplements resulted in 86,69% crude fat and 90,78% crude protein digestibility). Ducks fed with 4% shrimps head meal (R3) produced eggs with highest yolk pigment intensity (10,55). (Animal Production 9(1): 30-35 (2007) Key Words : shrimps head meal, L-Carnitine, digestibility, yolk pigment intensity